Potential Renewable Energy from Tofu Processing Waste in Banda Aceh City, Indonesia - Faisal, M.; Machdar, I.; Mulana, F.; Daimon, H. (Asian Journal of Chemistry, 2014)
The potential renewable energy from tofu processing industries in Banda Aceh city of Indonesia and their waste characteristics have been studied. There are 10 tofu processing industries in Banda Aceh with raw materials capacity ranging from 150-500 kg/day for each industry. Totally, about 45,900 kg of wastewater produced from 2,550 kg/day soybean in Banda Aceh. Currently, the waste has been disposed into the environment and river without any treatment, causing bad odours and pollution of the surface and ground water. The management of this waste with high water content represents an economic problem because of the high costs for disposal, treatment and/or use. The concentration of chemical oxygen demand (COD) from the tofu processing industries of Banda Aceh city is ranging from 5000-8500 mg/L, indicated that the waste has potential for bio energy production. About 128.52 m3/day of CH4 could be produced from 10 tofu processing industries in Banda Aceh.